(untitled) (Global Journal of Science Frontier Research, 2017)
In Ethiopia, a number of improved bread wheat (TriticumaestivumL.) varieties have been released by different research centers inorder to see the adaptability and performance of different bread wheat genotypes. However nothing has been done at Gurage Zone and therefore a total of twenty five bread wheat (TriticumaestivumL.) genotypes were evaluated for adaptability and performance at Gurage zone at two different environments. The genotypes were grown in randomized complete block design. Data were collected on 13 agronomic characters. Based on the mean separation, highest grain yield (4941.70kg/ha) was recorded from Hoggana, while lowest yield of (1983.30 kg/ha) was obtained from Kakaba and Sofumar at Fereziye. At Kotergedra, the highest grain yield of (5366.7 kg/ha) was also recorded from Hoggana and the lowest yield of (3166.7 kg/ha) was obtained from Kakaba. The highest above ground biomass also obtained from Hoggana at both location 10850.00 kg/ha and 16992.00 kg/ha at Fereziye and Kotergedra respectively. Statistically, the variety Hoggana gave the highest tillers per plant and spikes per plant at both locations those are positive contributions to grain yield.